Sentiment Analysis of Cigarette Use Based on Opinions from X Using Naive Bayes and SVM - Tundo; Eldina, Ratih; Setiawan, Kiki; Fajri, Raisah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The research employs Naive Bayes and Support Vector Machine (SVM) classification techniques to analyze attitudes toward cigarette consumption based on Twitter user opinions. Twitter, being one of the most popular social media platforms, serves as an excellent source for gauging public sentiment on various issues, including cigarette smoking, referred to here as